The coordinators i and z in Polish: A cognitive-typological approach (PART 1) - Andrason, Alexander (Lingua Posnaniensis, 2016)
Developed within the frame of cognitive and typological linguistics, the present study examines the taxonomical status of the lexemes i and z in Polish. To achieve this aim, the author analyzes the compliance of the two forms with the prototype of coordinate-hood and the structure of their maps of polyfunctionality. The evidence demonstrates that i is a canonical instantiation of the category of coordinate-hood while z is less canonical. Additionally, the two lexemes yield different maps of polyfunctionality (with distinct prototypicality nuclei), which reflects their distinct diachronic and conceptual origin. The map of i radiates from the value of ‘also’ while the map of z radiates from a comitative sense. This article – the first in a series of two – presents the framework underlying the research and introduces the empirical evidence related to the lexeme i.